2011
DOI: 10.4314/ajpsy.v14i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of primary health care providers towards people with mental illness: evidence from two districts in Zambia

Abstract: Objective: The aim of this study was to explore health care providers' attitudes towards people with mental illness within two districts in Zambia. It sought to document types of attitudes of primary health care providers towards people suffering from mental illness and possible predictors of such attitudes. This study offers insights into how health care providers regard people with mental illness that may be helpful in designing appropriate training or re-training programs in Zambia and other low-income Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 34 publications
15
71
0
4
Order By: Relevance
“…For example, a qualitative study that was done among primary health care professionals' perception of mental health among young people in Nicaragua found that most of the professionals had adequate information on mental illness among young people (Medina et al, 2014). Other studies have reported similar findings (Urada et al, 2012; Kapungwe et al, 2011;Winer et al, 2013). In comparing the nurses and the community health workers in the present study however, results revealed that the nurses were more aware of signs of mental illness in children and adolescents than the community health workers.…”
Section: Discussionsupporting
confidence: 68%
“…For example, a qualitative study that was done among primary health care professionals' perception of mental health among young people in Nicaragua found that most of the professionals had adequate information on mental illness among young people (Medina et al, 2014). Other studies have reported similar findings (Urada et al, 2012; Kapungwe et al, 2011;Winer et al, 2013). In comparing the nurses and the community health workers in the present study however, results revealed that the nurses were more aware of signs of mental illness in children and adolescents than the community health workers.…”
Section: Discussionsupporting
confidence: 68%
“…This is slightly more than in similar studies on attitudes from Zambia [32]. However, the reason why the health-care workers had this opinion was not further investigated in this study.…”
Section: Discussionmentioning
confidence: 58%
“…These include the priorities of donors, the lack of grassroots demands and political interest as well as the limited information and the prevalence of stigma. This stigma is perceived to affect primary health care providers as well as the wider population (22).…”
Section: Health Care Priorities and Resources For Mental Healthmentioning
confidence: 99%
“…However this has been challenged (22,23) and is now recognised as a widespread issue. In particular it is noted that this is fuelled by limited public information and a systemic failure to address issues of discrimination, including the continuing use of policies and legislation that restrict participation in civic life and limit possibilities for employment.…”
Section: Public Perceptionsmentioning
confidence: 99%